2013
DOI: 10.1073/pnas.1219333110
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 5-phosphate 4-kinase (PIP4K) regulates TOR signaling and cell growth during Drosophila development

Abstract: During development, Drosophila larvae undergo a dramatic increase in body mass wherein nutritional and developmental cues are transduced into growth through the activity of complex signaling pathways. Class I phosphoinositide 3-kinases have an established role in this process. In this study we identify Drosophila phosphatidylinositol 5-phosphate 4-kinase (dPIP4K) as a phosphoinositide kinase that regulates growth during larval development. Loss-of-function mutants in dPIP4K show reduced body weight and prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(127 citation statements)
references
References 32 publications
11
115
1
Order By: Relevance
“…These data indicate that Pip4k2a and PIP4k2b suppress PI3K-Akt activation but facilitate mTORC1 activation. This model is consistent with the observation that deletion of the single form of PIP4K2 in flies causes suppression of TORC1 activation and suppression of growth (7). To determine the epistasis among the multiple mammalian enzymes, phenotypes of the viable double knockout mice will need to be better examined.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These data indicate that Pip4k2a and PIP4k2b suppress PI3K-Akt activation but facilitate mTORC1 activation. This model is consistent with the observation that deletion of the single form of PIP4K2 in flies causes suppression of TORC1 activation and suppression of growth (7). To determine the epistasis among the multiple mammalian enzymes, phenotypes of the viable double knockout mice will need to be better examined.…”
Section: Discussionsupporting
confidence: 77%
“…Mackey et al argued that PI5P4Kγ was negatively regulated by mTORC1 through direct phosphorylation at serine 324 and serine 328 (6). On the other hand, it was reported that knocking out the only PI5P4K isoform in Drosophila resulted in lower body weight and that this correlated with decreased mTORC1 signaling (7). Of particular interest, multiple studies have shown a link between a SNP (rs1678542) in the human PIP4K2C locus and familial autoimmunity (8,9).…”
Section: Significancementioning
confidence: 99%
“…For example, stable knockout of Drosophila dPIP4K (orthologous to the highactivity PIP4K2A in higher species) results in a dramatic attenuation of Akt phosphorylation (20), whereas acute depletion of PIP4K2A in human leukocytes by RNAi results in increased Akt phosphorylation (19). No Akt phenotype was found in PIP4K2A knockout mice (21), but as far as we are aware, cells of the hematopoietic lineage were not studied there; another study from the same group elegantly showed the tissue variability of gene knockouts, with PIP4K2B knockout mice having enhanced insulininduced Akt phosphorylation in skeletal muscle and liver but not in white fat (22).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike PIPKI, the contribution of PIPKII enzyme in PI3K/Akt/mTORC1 appears less dominant and counteracting [40] as the majority of PI(4,5)P 2 is synthesized by PIPKI. However, studies in Drosophila still lend support to the role of PIPKII in cell growth and Akt/mTORC1 signaling ([41]. Additionally, phosphatidic acid which activates different isoforms of PIPKI inhibits endogenous inhibitor of mTORC1, suggesting that PIPKI provide another level of mechanism in regulating the PI3K/Akt/mTORC1 signaling in cancer [42, 43].…”
Section: Pipki/pipkii Control Of Pi3k/akt Activation In Cancermentioning
confidence: 99%